Computational model based on shannon entropy to analyze violence against women: A case study in Peru - Delgado, Alexi (2018)
Violence against women is a social problem that not only affects women involved, but also their relatives and their environment. In Peru, it is a topic that is becoming increasingly more visible. In this work, a computational model based on the entropy-weight method, which is an approach from Shannon entropy theory, was used. The entropy-weight method was applied to calculate the weights of the criteria; and then, the departments studied were classified according to the results of a weighted sum. The evaluation criteria were physical violence against women (C1), sexual violence (C2), psychological violence (C3), women who suffered violence and sought help (C4), reported cases of family or sexual violence (C5), gender inequality in the labor force (C6), and victims of femicide (C7). This article presents a map of information on the departments with the highest rate of violence against women. The results showed that the two departments with very high violence against women were Madre de Dios and Moquegua; and the two departments with low violence against women were Lambayeque and Amazonas. The method showed interesting results and could be applied to modeling other types of social problems.